Relationship between White Blood Count to Mean Platelet Volume Ratio and Clinical Outcomes and Severity of Coronary Artery Disease in Patients Undergoing Primary Percutaneous Coronary Intervention - Altekin Refik Emre; Kilinc Ali Yasar; Yanikoglu Atakan; Cicekcibasi Orhan; Kucuk Murathan (Hindawi-Wiley, 2020)
Background. The white blood cell count to mean platelet volume ratio (WMR) is an indicator of inflammation in patients with atherosclerotic disease. Residual SYNTAX Score (RSS) is an objective measure of degree and complexity of residual stenosis after percutaneous coronary intervention (PCI). We investigated the relationship between WMR and clinical prognosis and RSS in patients undergoing primary percutaneous coronary intervention (P-PCI). Method. Between June 2015 and December 2018, 537 patients who underwent primary PCI were evaluated for in-hospital events, and 477 patients were evaluated for clinical events during follow-up after discharge. The endpoint of our study is major adverse cardiac events (MACEs) seen in the in-hospital and follow-up periods. Results. In our study, 537 patients were stratified into two groups according to admission median WMR. There were 268 patients in the low WMR group (WMR<1286) and 269 patients in the high WMR group (WMR≥1286). RSS (p=0.01) value of the high WMR group was higher than that of the low WMR group. The rates of in-hospital MACE (p=0.001), cardiac death (p<0.001), decompansated heart failure (0.007), and ventricular tachycardia/fibrillation (p=0.003) were higher in the high WMR group than in the low WMR group. The follow-up MACEs (p=0.043), cardiac death (p=0.026), and reinfarction (p=0.031) ratio were higher in the high WMR group. In ROC analysis, cut-off values of in-hospital and follow-up MACEs were >1064 (sensitivity: 83.12%, and specificity: 36.29%) and >1130 (sensitivity: 69.15%, and specificity: 44.91%), respectively. The Kaplan-Meier analysis showed that the high WMR group had the significantly lowest MACE-free survival rate (log-rank test, p=0.006). A moderate correlation was observed between WMR and RSS (r: 456, p=0.002). Conclusion. A higher WMR value on admission was associated with worse outcomes in patients with P-PCI and independently predicted for follow-up MACEs. The WMR provides both a rapid and an easily obtainable parameter to identify reliably high-risk patients who underwent primary percutaneous coronary intervention due to STEMI.